Micropropagation of Populus euphratica Using BAP, ISK, NSK and IMK under Saline Conditions in Uzbekistan - Otayeva Ziyoda Ergash qizi; Yusupov Ulugbek Karim ugli (American Journal of Biology and Natural Sciences, 2025)
Populus euphratica is a drought-resistant tree species indigenous to dry and saline areas of Central Asia. Its ecological function in stabilising damaged landscapes in Uzbekistan is well documented; yet, natural regeneration is ineffective due to low seed viability and inadequate field survival. This research sought to establish a dependable in vitro micropropagation methodology utilising explants from indigenous populations. Experiments were performed from 2023 to 2024 at the Biotechnology Laboratory of the National University of Uzbekistan. Nodal and apical segments were cultivated on MS medium augmented with BAP and ISK for shoot induction, subsequently rooted in White medium containing IMK. The optimal shoot induction (92%) and an average of 5.1 shoots per explant were achieved with 1.5 mg/L BAP and 0.5 mg/L ISK. Rooting was most effective with 1.0 mg/L IMK in White medium, resulting in an 85% rooting rate and an average root length of 5.8 cm. Plantlets were acclimatised in a peat:sand:perlite mixture under greenhouse conditions, achieving an 82% survival rate. All phases of regeneration were subjected to statistical analysis via ANOVA and Duncan’s test (p < 0.05). The established technique has significant reproducibility, morphogenic stability, and practical applicability for the restoration of saline and dry ecosystems in Uzbekistan. These findings provide a scalable approach for the extensive dissemination of P. euphratica, aiding national initiatives in ecological restoration and desertification mitigation.